The Costs and Benefits of Thai Commercial Banks to the Implementation of Basel II - Musignisarkorn, Orin (2009)
It is recognized that Basel II implementation is an international challenge for both banks and supervisions. The implementation of Basel II is not only a compliance issue but the industry participants must also consider the ultimate goal of the soundness and stability of the baking system. In order to implement Basel II effectively, both banks and the supervisions must understand and comprehend its assumption, constrains and implication. Although there is a beneficial part on the risk measurement and standard framework, there are still many areas that banks need to study and explore. Nevertheless, Thai commercial banks will face the great challenges in collecting and validating the data, training the staff and employee, comprehending the laws and regulations and innovation of their own IT plat form. In short term our Thai commercial banks might fall behind in adjusting their management and components of the bank but I strongly believe that in the long run, implementation of Basel II will leads to a betterment of the banking sector and will strengthen the financial stability in the years to come.